Сontribution of the department of propaedeutics of internal diseases at Saratov State Medical University to practical healthcare: a historical perspective - I. A. Gordeev; O. M. Posnenkova; A. R. Kiselev; V. I. Gridnev; T. M. Bogdanova (Кардиоваскулярная терапия и профилактика, 2023)
The objective of the study was to analyze the contribution of the Department of Propaedeutics of Internal Diseases at Saratov State Medical University to practical healthcare, depending on the historical context of its work. Articles contained in the eLibrary and CyberLeninka databases, as well as data from open Internet sources about the history of the department, were analyzed. The obtained data are compared with the historical events of the corresponding period. It was shown that mutually beneficial cooperation between the clinic, the department and the research institute seem to be a reliable and economical form of introducing new medical care technologies into practical healthcare.